Increasing Students' Interest in Computer Science Through Computer Simulation Models - Isayev Nurbek Faxriddin o`g`li; Isayeva Sarvinoz Boytemir qizi (Scholars Digest Publishing, 2023)
The article presents methods of formation and development of students' potential to apply the knowledge they have acquired in computer science to life, connecting their practical activities with broadening their outlook on computer science based on computer simulation models.
Keywords: virtual laboratory, multimedia programs, graphics, video, photo information, computer simulation model and visualization.